Clinical study on orthopaedic treatment of chronic osteomyelitis with soft tissue defect in adults. Issue 6 (21st December 2021) - Zhang, Xinling; Yang, Xin; Chen, Yujie; Wang, Guanhuier; Ding, Pengbing; Zhao, Zhenmin; Bi, Hongsen
Abstract: To investigate the clinical application value of different flap transfer and repair techniques in adult patients with chronic osteomyelitis of limbs complicated with soft tissue defects. According to the characteristics and defects of 21 cases, different plastic surgery was applied, including debridement, negative pressure device, and tissue flap to cover wound. Among 21 cases of chronic osteomyelitis complicated with local soft tissue defect, 15 patients were repaired with sural neurotrophic musculocutaneous flap transfer, 2 patients were repaired with medial plantar skin flap transfer, 2 patients were repaired with ilioinguinal skin flap transfer, 1 patient was repaired with z‐forming wound, and 1 patient was repaired with soleus muscle flap combined with full‐thickness skin graft. All the 21 patients underwent bone cement implantation after dead bone osteotomy. Among them, 19 patients underwent bone cement replacement with 3D prosthesis within 6 months to 1 year after surgery, and 2 patients carried bone cement for a long time. Early intervention, thorough debridement, removal of necrotic or infection, and then selecting the appropriate wound skin flap coverage are important means of guarantee slow osteomyelitis wound healing and for providing a possible way to permanent prosthesis implantation subsequently.